Rheological and thermogelling properties of commercials chitosan/β-glycerophosphate: Retention of hydrogel in water, milk and UF-milk. (February 2017) - Taherian, Ali R.; Lacasse, Pierre; Bisakowski, Barbara; Pelletier, Marylène; Lanctôt, Samuel; Fustier, Patrick
Abstract: This study shows that how commercial chitosans owing three different molecular weights and high degree of acetylation can be neutralized closed to physiological pH using β-glycerophosphate to produce liquid solution at room temperature and formation of hydrogel upon subsequence heating up to the biological temperature (37 °C). The addition of β-glycerophosphate provided the precise buffering, controlled hydrophobic interaction and hydrogen bonding in order to retain chitosan in solution at 22 °C and neutral pH, and allowed gel formation upon heating up to 37 °C. Examination of flow and dynamic rheological properties, extrusion force and energy, heat induced gelation and gel stability of selected chitosan evidenced the flow performance and frequency dependent of elastic and viscous modules, extrusion ability, establishment of sol/gel diagram and retention of gel in three food mediums including water, pasteurized milk and ultrafiltered milk. It appeared that strength of gel network is governed by molecular weight and the higher molecular weight provided the superior gel strength. The study on retention of selected hydrogel in different mediums revealed that water has the most affinity to maintain the gel network. Graphical abstract: Highlights: Acidic chitosans neutralized by β-Glycerophosphate provided gel at 37 °C. Viscoelastic properties of commercial chitosan vary based on molecular weight. Molecular weight of chitosan governs the strength of gel network. The stability of hydrogel varies based on the type of holding medium.